Light without TORCH: Periventricular Haemorrhage and Group B Streptococcal Meningitis in a Neonate - Duddy, John C; Kaliaperumal, Chandrasekaran; Sattar, Muhammed T (Biology, Engineering, Medicine and Science Reports)
Post-infectious hydrocephalus is a common entity needing attention of paediatricians and neurosurgeons. Periventricular Haemorrhage (PVH) affects both preterm and term babies. Risk factors include male gender, short gestation, labour and vaginal delivery. Congenital infections such as Toxoplasma and CMV are associated with hydrocephalus and intracranial calcification. We present an unusual association of Group B Streptococcal infection with periventricular haemorrhage. A Caucasian female was born at 37 weeks gestation by normal vaginal delivery. Birth weight was 2.72kg and OFC was 33cm (50th centile). There were no antenatal problems or maternal infections. On day 2 of life, the patient presented with unusual cry, lethargy and reduced feeding. Group B Streptococcal meningitic septicaemia was confirmed with positive CSF and blood cultures. At 7 weeks, she presented with a two-week history of increasing head circumference. Ventriculo Peritoneal (VP) shunt was inserted for post-infectious hydrocephalus. There was difficulty in waking the patient up post-operatively and subsequent CT Brain showed the presence of multiple high attenuation foci in the periventricular region suggestive of haemorrhage or calcification. MR imaging confirmed numerous foci of abnormal signal intensity in the periventricular white matter, most likely blood products. To our knowledge, this is the first report of an association between Group B Streptococcal meningitis and PVH.
Keywords: Periventricular haemorrhage; Group B Streptococcus; Meningitis; Neonate